KOMPOSISI SILASE IKAN DAN TELUR KEONG MAS (Pomacea canaliculata) SEBAGAI PAKAN UNTUK PERTUMBUHAN IKAN SIDAT (Anguilla marmorata) - Hikma, Hikma; Tantu, Fadly Y; Tobigo, Desiana Trisnawati (FAPETKAN UNTAD, 2016)
Eel has economic value is a species of fish that are sold on the international market, Karnan containing vitamins and micronutrients are very high. The research objective was to determine the effect of silage by substitution of fish meal and eggs of snails (Pomacea canaliculata) to the growth of fingerling eels (Anguilla marmorata). This study was conducted from November 2014 - January 2015. Research laboratory housed in Agricultural Technology (THP) Tadulako University, Palu. The raw material for the manufacture of feed that is, fish silage, egg flour, bran flour, tapioca starch, vitamins and minerals. Feed is made in the form of fish paste. Eating in eel fingerlings that every day as much as 5-10% of the total weight of fish per day. Eat twice a day, morning and afternoon har. The study design completely randomized design (CRD), with 3 treatments and 6 replications. Treatment A: 90% + 10% egg fish silage flour; Treatment B: 80% + 20% egg fish silage flour; Treatment C: 70% + 30% egg fish silage flour. With the ever-dose comparisons between fish silage and flour (90: 10) (treatment A) can promote the growth, survival and feed efficiency was good.Â Key words: eggs, snails, growth, Anguilla marmorata